Heterogeneity in Maltreated and Non‐maltreated Preschool Children's Inhibitory Control: The Interplay Between Parenting Quality and Child Temperament. Issue 5 (27th May 2013) - Cipriano‐Essel, Elizabeth; Skowron, Elizabeth A.; Stifter, Cynthia A.; Teti, Douglas M.
<x xml:space="preserve">Abstract</x> This study examined the contribution of child temperament, parenting, and their interaction on inhibitory control development in a sample of maltreated and non‐maltreated preschool children. One hundred and eighteen mother–child dyads were drawn from predominantly low‐income, rural communities. Dyads participated in a laboratory session in which maternal warm autonomy support, warm guidance, and strict/hostile control were observationally coded during a joint teaching task. Independent assessments of children's inhibitory control were obtained, and observers rated children's temperament. After relevant covariates, including income, maternal education, and child age and IQ were controlled for, there were no differences between the maltreatment and non‐maltreatment groups in either children's inhibitory control or mothers' behaviours in the laboratory session. Even after much of the variance in children's inhibitory control was accounted for from the covariates, children's temperamental negativity moderated the effects of warm autonomy support on inhibitory control in both maltreatment and non‐maltreatment groups. Temperamentally negative children whose mothers displayed more warm autonomy support showed greater inhibitory control, at levels on par with low‐negative children. Findings suggest that heterogeneity in children's self‐regulation may be due in part to individual differences in sensitivity to caregiver support for children's independence, even among those exposed to maltreatment. Copyright © 2013 John Wiley & Sons, Ltd.